AGRIBUSINESS FAMILY: AN APPROACH USING COST INFORMATION - Guse, Jaqueline Carla; Horz, Vagner; Nunes, Camile Melez; Rossato, Marivane Vestena; Dörr, Andréa Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708773 Accounting is the science that studies the Shareholders of the companies and people. With the market increasingly competitive, we have noticed an increasing use of accounting information in organizations as a tool to aid in decision making. To keep this market, the farmer has used new technologies in their quest to produce higher quality products. Concurrently, we have used the Cost Accounting as an essential tool to keep your product competitive. Due to this situation, this paper aims to evaluate the use of accounting information in the writing process of the production cost of agricultural industries in the municipality of Santa Maria-RS. For this, a survey was conducted with a sample of 25 agribusinesses in the municipality. This research was based on a semi-structured questionnaire, which contained open questions in order to achieve the particularities of each project. The results show that most owners of agribusinesses have knowledge of cost accounting records and performs most cost notebooks or papers in many. Still, more than half of agribusinesses studied whether the use of cost accounting information for the pricing of products, benefiting, since the cost of products is the basis of the selling price.